The Implementation of Character Management Through Habit At SDIT Nurul Huda Purbalingga - Dirsan Dirsan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The cause of low character is the education system that emphasizes intellectualdevelopment rather than character development. Efforts in character education forstudents are by inculcating character through habituation. This study aims to describe andcritically analyze the Cultivation of Character Through Habituation at SDIT Nurul HudaPurbalingga. This type of research is field research or field research where researchers godirectly to the field to obtain data and information related to the research conducted. Theactivities carried out were time discipline, practicing 3S and kissing the teacher's handwhen the child shook hands with the teacher, morning tahsinul qiro'ah, dhuha prayer,praying in congregation, asking permission, eating according to etiquette, not eatingsnacks outside school, and other. The implementation of character planting throughhabituation is carried out through 3 stages, namely the stage of knowledge (knowing),implementation (acting), and habituation (habit). The creation of a conducive atmosphereand adequate facilities also support the process of implementing character through routinehabituation.